WOMEN AS UMRAH GUIDES: A GENDER PERSPECTIVE IN HAJJ AND UMRAH MANAGEMENT - Nur Iffatul Ainiyah; Abdul Rozaq (Universitas Islam Negeri Imam Bonjol Padang, 2026)
The organisation of Umrah pilgrimages in Indonesia in recent years has shown a significant increase in the number of female pilgrims compared to male pilgrims. This situation has created specific needs in terms of religious guidance, particularly with regard to the biological, psychological and social aspects experienced by female pilgrims. However, the reality on the ground shows that the number of female religious guides is still limited and their role has not yet been fully recognised structurally within the Hajj and Umrah management system. This study aims to analyse the role of women as umrah pilgrimage guides (muthowwifah) and examine the challenges and opportunities from a gender perspective in hajj and umrah management. This study uses a descriptive qualitative approach with a case study design. Data was collected through field observations, in-depth interviews, and documentation of muthowwifah and female pilgrims who received direct guidance. The organisation of Umrah pilgrimages in Indonesia in recent years has shown a significant increase in the number of female pilgrims compared to male pilgrims. The results of the study show that: (1) muthowwifah play a strategic role, not only in providing technical guidance on worship, but also in providing moral support, motivation, and assistance with issues specific to women's worship, such as menstrual management during Umrah; and (2) muthowwifah face a number of challenges, including strong gender stereotypes, limited access to professional training and certification, and the lack of formal recognition of the profession. This study recommends strengthening affirmative policies through continuous training, professional certification, and the integration of a gender perspective in hajj and umrah management. The novelty of this study lies in its affirmation of the role of women as strategic actors in hajj and umrah management oriented towards gender justice.